A Critical Review of Properties and Analytical/Bioanalytical Methods for Characterization of Cetuximab. (3rd March 2020) - Hanck-Silva, Gilmar; Fatori Trevizan, Lucas Noboru; Petrilli, Raquel; de Lima, Felipe Tita; Eloy, Josimar O.; Chorilli, Marlus
Abstract: Cetuximab (CTX) is a chimeric monoclonal antibody (mAb) able to selectively bind to the epidermal growth factor receptor (EGFR), resulting in inhibition of EGF linkage and phosphorylation cascade interruption. As a result, it is able to prevent cell proliferation, angiogenesis and metastasis, usually related to cancer malignization. As the EGFR is overexpressed in many human tumors, its use has been approved by FDA since 2006. Clinical use of CTX has been proved to cause skin rash which is related to the better prognosis. Thus, currently strategies also focus on the development of safe and effective drug delivery systems and on quantification methods for CTX in a variety of matrices. Based on the challenges to quantify CTX, immunoassays, spectrophotometric assays, electrophoretic assays and chromatographic assays are under study. Among them, the spectrophotometric/colorimetric techniques, used in near 32% of the papers investigated, followed by chromatographic techniques and immunoassay methods, such as enzyme-linked immunosorbent assay (ELISA), used in 29% and 26%, respectively, and electrophoretic techniques used in near 13%. Herein, we will describe and discuss CTX main aspects and highlight the main quantification methods that are currently used for its quantification in different matrices.